RETRACTED: Dependence of microbiological activity of alluvial soils of irrigated meadow of Bukhara oasis on salinity levels - Bo’riyeva Dilorom; Xalilova Ma’mura; Atayeva Zamira (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001